2019
DOI: 10.1016/j.ccell.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Responses in the Absence of Toxicity in Solid Tumors by Targeting B7-H3 via Chimeric Antigen Receptor T Cells

Abstract: SUMMARY The high expression across multiple tumor types and restricted expression in normal tissues make B7-H3 an attractive target for immunotherapy. We generated chimeric antigen receptor (CAR) T cells targeting B7-H3 (B7-H3.CAR-Ts) and found that B7-H3.CAR-Ts controlled the growth of pancreatic ductal adenocarcinoma, ovarian cancer and neuroblastoma in vitro and in orthotopic and metastatic xenograft mouse models, which included patient-derived xenograft. We also found that 4–1BB co-stimulation promotes low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
339
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(353 citation statements)
references
References 57 publications
(85 reference statements)
14
339
0
Order By: Relevance
“…Meanwhile, we showed overexpression of membranous B7-H3 in a variety of human malignancies, but minimal staining of B7-H3 protein in the cytoplasm of normal tissues that were largely limited in focal liver cells and a few luminal epithelial cells of the stomach and colon, which is consistent with previous reports. 12 Therefore, B7-H3 specific CAR-T cells are expected to have minimal toxicity in normal tissues. Nevertheless, potential toxicities upon recognition of the antigen expressed in normal tissues require further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, we showed overexpression of membranous B7-H3 in a variety of human malignancies, but minimal staining of B7-H3 protein in the cytoplasm of normal tissues that were largely limited in focal liver cells and a few luminal epithelial cells of the stomach and colon, which is consistent with previous reports. 12 Therefore, B7-H3 specific CAR-T cells are expected to have minimal toxicity in normal tissues. Nevertheless, potential toxicities upon recognition of the antigen expressed in normal tissues require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…11 While it appears that B7-H3 mRNA is ubiquitously expressed in various mouse and human tissues under normal conditions, immunohistochemical (IHC) analysis demonstrates that the expression of its protein is limited to a select subset of tissues. 12,13 Interestingly, B7-H3 protein is frequently upregulated in the majority of solid human tumors such as prostate cancer, non-small-cell lung cancer, pancreatic cancer, breast cancer, ovarian cancer and colorectal cancer [14][15][16][17][18][19][20][21][22][23][24] and within the tumor vasculature as well. 25 Several studies have also shown that B7-H3 overexpression is associated with tumor progression, metastatic potential and a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CAR-T cells that were genetically engineered to graft specific recognition ability for T cells were generated with B7-H3 as the target [56]. In this research, they explored the treatment efficacy of CAR-T cells targeting B7-H3 on pancreatic ductal adenocarcinoma, ovarian cancer, and neuroblastoma, both in vitro and in orthotopic and metastatic xenograft mouse models including patient-derived xenograft.…”
Section: Targeting B7-h3 Therapymentioning
confidence: 99%
“…While the mentioned results are reassuring regarding saftey of CAR T cell therapy, different strategies are currently under investigation to further improve the safety profile of CAR T cells. These strategies include: (I) modification of the chimeric antigen receptor cell itself [85,86]; (II) identification of predictive biomarkers for CAR T cell toxicity [84]; (III) "safety switches" such as inducible suicide genes [87]; and (IV) novel drugs to mitigate CRS and NE [88].…”
Section: Chimeric Antigen Receptor T Cellsmentioning
confidence: 99%